2015
DOI: 10.1016/j.jmii.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics and virulence factors in methicillin-susceptible, resistant, and heterogeneous vancomycin-intermediate Staphylococcus aureus from central-southern China

Abstract: The prevalence of hVISA was considerably high in central-southern China. Simultaneous carriage of multiple virulence genes was common in S. aureus isolates; the virulence genes were more diverse and frequent among MSSA isolates than among MRSA isolates. Furthermore, the distribution of some virulence genes was correlated with the different S. aureus CCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 30 publications
3
44
3
Order By: Relevance
“…Further, reports of MRSA from Korea showed that 11 out of 17 mastitic strains from five different farms belonged to a single spa type (t324) and report from the USA found that all strains (n = 4) belonged to similar spa (t121) type [8]-[9]. Among the strain types that we found, spa types t2526 and t9602 have been previously reported in human infections [37]-[38]. Other spa types were well documented in both human and bovine infections or in bovine mastitis except spa types, t3731 and t8137 for which no published reports could be found.…”
Section: Discussionsupporting
confidence: 50%
“…Further, reports of MRSA from Korea showed that 11 out of 17 mastitic strains from five different farms belonged to a single spa type (t324) and report from the USA found that all strains (n = 4) belonged to similar spa (t121) type [8]-[9]. Among the strain types that we found, spa types t2526 and t9602 have been previously reported in human infections [37]-[38]. Other spa types were well documented in both human and bovine infections or in bovine mastitis except spa types, t3731 and t8137 for which no published reports could be found.…”
Section: Discussionsupporting
confidence: 50%
“…A study conducted in Minnesota and Wisconsin found that CA-MRSA strains were likely to contain the lukED locus (~99%), whereas MSSA strains collected from either symptomatic patients or asymptomatically colonized human subjects were less likely to contain the locus (44–77%) [63]. These numbers are similar to previous studies that estimated 87–93% carriage rate in Japanese clinically acquired strains (no drug-resistance noted) and 88–99% in CA-MRSA strains acquired around the world [62, 86, 88]. Interestingly, the lukED locus is also present in ~90% of S. aureus strains collected from cows with subclinical to severe mastitis, supporting a possible role for LukED in virulence or infectivity in different host species [84, 89].…”
Section: Overviewsupporting
confidence: 82%
“…On the other hand, the LCM isolates were SCC mec type IV or V and nearly half had PVL genes, which indicated genetic relatedness to community-acquired MRSA (CA-MRSA) isolates that have a higher prevalence of PVL (Liu et al, 2015). Therefore, the tested isolates somewhat represent the major types of clinical MRSA isolates.…”
Section: Discussionmentioning
confidence: 99%